Prosodic cue use for identifying interrogative and declarative structures with wide and narrow focus in individuals with and without aphasia - Schneider, Kathleen; Tuomainen, Outi; Wartenburger, Isabell; Hanne, Sandra (Frontiers in Communication, 2025)
IntroductionProsody plays a critical role in linguistic processing at both sentential and information-structural levels, while prosodic impairments in individuals with aphasia can lead to difficulties in sentence comprehension and everyday communication. Despite its importance, prosodic processing in aphasia and its relationship to inter-individual variability within this highly heterogeneous population remain underexplored. This study examined prosodic cue use for structural prediction in individuals with and without aphasia, exploring individual differences in prosodic impairments.MethodsSixteen individuals with aphasia and thirty neurotypical control participants completed a sentence type identification task using string-identical (i.e., structurally ambiguous) German sentences (interrogative vs. declarative) presented under two focus conditions (wide vs. narrow). Response accuracy and reaction times were analyzed using linear mixed-effects models. To explore variability among individuals with aphasia, a clustering analysis was conducted based on task performance.ResultsIndividuals with aphasia demonstrated significant difficulties in prosodic processing, particularly in identifying questions under wide focus conditions. Wide focus posed challenges for structural prediction due to deficient prosodic cue use, while narrow focus facilitated task performance by providing more salient prosodic cues. The level of speech fluency and abilities in global pitch detection emerged as potential sources of variability. Clustering analysis identified distinct subgroups of individuals with aphasia, each of which was characterized by unique patterns of task performance, suggesting differential underlying mechanisms potentially linked to cognitive abilities and overall processing demands.DiscussionThese findings emphasize challenges and resources of prosodic cue use for structural prediction, advancing the understanding of prosodic impairments and their effects on communication. This study underscores the importance of considering individual differences in prosodic processing for developing targeted diagnostic tools and therapeutic approaches tailored to the needs of individuals with aphasia.